An organoid‐derived bronchioalveolar model for SARS‐CoV‐2 infection of human alveolar type II‐like cells. (11th January 2021) - Lamers, Mart M; van der Vaart, Jelte; Knoops, Kèvin; Riesebosch, Samra; Breugem, Tim I; Mykytyn, Anna Z; Beumer, Joep; Schipper, Debby; Bezstarosti, Karel; Koopman, Charlotte D; Groen, Nathalie; Ravelli, Raimond B G; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) causes coronavirus disease 2019 (COVID‐19), which may result in acute respiratory distress syndrome (ARDS), multiorgan failure, and death. The alveolar epithelium is a major target of the virus, but representative models to study virus host interactions in more detail are currently lacking. Here, we describe a human 2D air–liquid interface culture system which was characterized by confocal and electron microscopy and single‐cell mRNA expression analysis. In this model, alveolar cells, but also basal cells and rare neuroendocrine cells, are grown from 3D self‐renewing fetal lung bud tip organoids. These cultures were readily infected by SARS‐CoV‐2 with mainly surfactant protein C‐positive alveolar type II‐like cells being targeted. Consequently, significant viral titers were detected and mRNA expression analysis revealed induction of type I/III interferon response program. Treatment of these cultures with a low dose of interferon lambda 1 reduced viral replication. Hence, these cultures represent an experimental model for SARS‐CoV‐2 infection and can be applied for drug screens. Synopsis: In vitro investigation of human lung alveolar physiology has remained difficult. Here, establishment and profiling of an organoid‐derived bronchioalveolar tissue culture allows analysis of SARS‐CoV‐2 cellular tropism and testing of treatment strategies for respiratory syndromes. Bronchioalveolar‐like cells derived from self‐renewing human fetal lung organoids give rise to a 2D human bronchioalveolar‐like model with air‐exposed apical side. In these cultures, alveolar type‐2‐like cells are particularly permissive to SARS‐CoV‐2 infection. SARS‐CoV‐2 infection induces a type‐I/III interferon host response in vitro. SARS‐CoV‐2 viral titers are sensitive to low dose interferon lamda 1 treatment. Abstract : A human airway in vitro culture permissive to COVID‐19 demonstrates a drug‐sensitive IFN response.